The Link between Life Effectiveness, Well-Being and Life Satisfaction Among Communities of Sepanggar Island in Sabah - Chua, Bee Seok; Getrude Cosmas; Saidatul Nornis Hj. Mahali (2018)
The purpose of this study was to investigate the link between life effectiveness, well-being and life satisfaction among members of the Sepanggar Island community. In addition to that, the aim was also to gauge the relationship between these variables according to the different generations of the island’s resident. A random sample of 124 people living at Sepanggar Island, Sabah (aged 65 to 97) responded to a questionnaire that included the following scales: The WHO-5 Well-being Index; The Satisfaction with Life Scale (SWLS); and The Satisfaction with Life Scale (SWLS). Findings suggested that the community members of the Sepanggar Island who were able to initiate action in new situations reported higher well-being. The subscales of time management and social competence contributed significantly and positively on the community members’ life satisfaction. The findings showed that life effectiveness of Generation X contributed higher variance in well-being as compared to the life effectiveness among Generation Y. The results also reported that the subscales of intellectual flexibility; task leadership and active initiative were the significant predictor of well-being among Generation X. Contrary, emotion control was the only significant predictors of well-being among Generation Y. The subscale of social competence was the only significant predictor of life satisfaction among Generation X of Sepanggar Island. But, for Generation Y, besides social competence, active initiative was also a significant predictor for their life satisfaction.